Epidemiology of Schistosomiasis in Egypt: Travel through Time: Review - Rashida M.R. Barakat (Journal of Advanced Research, 2013)
Schistosomiasis is a parasitic disease caused by blood flukes (Trematodes) of the genus Schistosoma (S.). It is well documented that schistosomiasis haematobium was endemic in Ancient Egypt. Infection was diagnosed in mummies 3000, 4000 and 5000 years old. Scott was the first to describe the pattern of schistosomiasis infection in Egypt. Schistosomiasis haematobium was highly prevalent (60%) both in the Nile Delta and Nile Valley South of Cairo in districts of perennial irrigation while it was low (6%) in districts of basin irrigation. Schistosoma mansoni infected 60% of the population in the Northern and Eastern parts of the Nile Delta and only 6% in the Southern part. Neither S. mansoni cases nor its snail intermediate host were found in the Nile Valley South of Cairo. The building of the Aswan High Dam -which was completed in 1967 – did not cause any increase in schistosomiasis prevalence. In 1990, a study conducted in nine governorates of Egypt confirmed the change in the pattern of schistosomiasis transmission in the Delta. There was an overall reduction in S. mansoni prevalence while Schistosoma haematobium had continued to disappear. In Middle and Upper Egypt there was consistent reduction in the prevalence of S. haematobium except in Sohag, Qena, and Aswan governorates. However, foci of S. mansoni were detected in Giza, Fayoum, Menya and Assiut. All schistosomiasis control projects implemented in Egypt from 1953 to 1985 adopted the strategy of transmission control and were based mainly on snail control supplemented by anti-bilharzial chemotherapy. In 1997, the National Schistosomiasis Control Program (NSCP) was launched in the Nile Delta. It adopted morbidity control strategy with Praziquantel mass treatment as the main component. In 1996, before the NSCP, 168 villages had S. mansoni prevalence >30%, 324 villages 20–30% and 654 villages 10–20%. By the end of 2010, in the whole country only 29 villages had prevalence >3% and none had more than 10%.